1998
DOI: 10.1515/tjj.1998.15.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dump Gap on Velocity Distribution and Flow Split in a Prototype Reverse-Flow Gas Turbine Combustor

Abstract: Flow characteristics in the outer annular passage of a prototype reverse-flow combustor have been experimentally investigated and reported in this paper. Emphasis has been placed on understanding the effect of a dump gap, close to the turn-section, on the nature of flow split through various holes on the outer liner surface. Study revealed that a dump gap plays a significant role in deciding the nature of flow in the annular passage and the relative flow split. It revealed that a 2 mm dump gap gives an optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The presence of an imposed stream wise adverse pressure gradient promotes more rapid mixing and spreading of the shear layer in the initial mixing region, elevated turbulent normal stresses and shear stress levels in the outer portion of the mixing layer after the inner and annular streams have merged [9]. Bharani et al [5] have reviewed literature on experimental studies -both isothermal and combustion -and prediction studies on coaxial jets, transverse jets and realistic liner geometries. In respect of coaxial jets, though mostly on swirling flows, they have listed the findings with regard to development of flow.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of an imposed stream wise adverse pressure gradient promotes more rapid mixing and spreading of the shear layer in the initial mixing region, elevated turbulent normal stresses and shear stress levels in the outer portion of the mixing layer after the inner and annular streams have merged [9]. Bharani et al [5] have reviewed literature on experimental studies -both isothermal and combustion -and prediction studies on coaxial jets, transverse jets and realistic liner geometries. In respect of coaxial jets, though mostly on swirling flows, they have listed the findings with regard to development of flow.…”
Section: Introductionmentioning
confidence: 99%
“…The compact reaction zone causes the fuel evaporation distance to be shortened, which affects combustion efficiency and stability. The study of reverse-flow combustors has attracted the attention of many scholars [6][7][8][9][10][11][12][13][14]. For example, Bharani et al [9] showed that the flow characteristics and flow distribution of the jet holes of a reverse-flow combustor change when the flow characteristics of the outer annulus were altered.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the authors clarified the flow characteristics of the inlet airflow with different swirling intensities in the outer circular channel of the reserve-flow combustor. Lastly, they investigated the effects on jets from different jet holes [9,10]. Currently, on account of compact structures, researchers mainly adopt probes and numerical simulations to examine the flow field characteristics and combustion performance in the reverse-flow combustor.…”
Section: Introductionmentioning
confidence: 99%